Вдосконалений метод розрахунку параметрів кінетики контактного обміну - Майзеліс, Антоніна Олександрівна (Київський національний університет технологій та дизайну, 2019)
An improved method of determining the parameters of the contact exchange kinetics is proposed. It uses nonlinear polarization curves of the coupled processes of negative metal dissolution and positive metal deposition. It is shown, that the maximum value of the current density of contact exchange between zinc anodes of the working pyrophosphate-citrate bath and its low-concentrated solution is 0.4 mA/cm2 and it is reached in a few seconds. It corresponds to the region of potentials of active dissolution of the zinc anode and deposition of a compact Ni layer. After that the contact exchange current reduces and stabilizes at a value of 0.27 mA/cm2. .
Improved Method of Calculation of Contact Exchange Kinetics Parameters
Keywords: contact exchange; Zn-Ni alloy; zinc anode; Ni deposition; контактний обмін; Zn-Ni сплав; цинковий анод; осадження сплаву Zn-Ni; осадження Ni